Smart water quality IoT-based system for healthy living - Amir, A.N. (Alpha Publishers, 2020)
In order to avoid the risk of drinking contaminated water, the information of drinking water quality must be available in real time. This paper presents the design and development of a real time monitoring system of drinking water quality using Internet of Thing (IoT). Several sensors IoT water sensors are used to measure and validate the water quality parameter values. These parameters include pH, turbidity and oxidation-reduction potential (ORP). The sensors are connected through an Arduino UNO controller. The Arduino UNO controller reads and sends sensor parameter values to an android mobile application which displays the measurements and concludes whether the quality of the water is safe to be drinkable or not. Â© 2020 Alpha Publishers.